Hyponatraemia and neurological complications in children admitted with bronchiolitis. (2nd July 2016) - Al Shibli, Amar; Abukhater, Dima; Al Kuwaiti, Najla; Noureddin, Muhammad Bassel; Al Harbi, Mariam; Al Kaabi, Aysha; Al Kaabi, Salwa; Hamie, May; Al Amri, Abdulla; Narchi, Hassib
Abstract : Background: Hyponatraemia occurs during bronchiolitis, sometimes with neurological manifestations. The prevalence of the latter differs widely and little is known about the time of occurrence and associated factors. This study was undertaken to investigate these complications. Methods: This was a retrospective observational chart review of a cohort of 233 infants under 2 years of age admitted with bronchiolitis to a teaching hospital in the United Arab Emirates. Results: Hyponatraemia (serum sodium <135 mmol/L) occurred in 105 infants (45%, 95% CI 38–51). Hyponatraemia was present on admission in 84 infants (80%) with 90% of cases occurring within 6 days of the onset of illness. It was mild (130–135) in 100 infants (95%) and severe (<130) in five (5%). It was not significantly associated with age, duration of illness before admission, viral aetiology, white cell count or serum C-reactive protein concentrations, or the volume of administered intravenous fluid or use of 0.18% sodium chloride (NaCl). Neurological manifestations occurred in a 29-day-old child with a serum sodium level of 123 mmol/L while receiving two-thirds intravenous maintenance fluids (0.18% NaCl). His developmental milestones remained normal on follow-up to the age of 5 years. Conclusion: Hyponatraemia is common in infants with bronchiolitis and occurs in the majority within 6 days of onset of symptoms. There was a significant association between the presence of fever (>38°C) on admission and the duration of hospitalisation.